Examination of Friction Stir-Welded AA 6262/5456 Joints through the Optimization Technique - S. Vijayakumar; Selvaraj Manickam; Suresh Seetharaman; T.V.Janardhana Rao; Devabalan Pounraj; Hari Prasadarao Pydi (Advances in Materials Science and Engineering)
Friction stir welding (FSW) is the solid state welding technique which is mostly utilized to join similar and dissimilar Al, Cu, Mg, and their alloys. This research investigated that the tensile strength of FSW dissimilar Al6262 and Al5456 of 4 mm thickness is carried out using an H-13 tool pin along with different process variables such as tool rotational speed (TRS), welding speed (WS), and tool tilt angle (TTA). The selected parameters are set as TRS of 900, 1100, and 1400 rpm, WS of 20, 30, and 40 mm/min with TTA of 2, 2.5, and 3° to find out significant parameters on tensile strength (TS). The Taguchi L27 method is taken to create a number of experiments to recognize the optimal level of each parameter to accomplish the highest TS value. From the experimental results witnessed, the extreme TS (202.44 MPa) is acquired at sample 22 when maintaining TRS-1400 rpm, WS-30 mm/min, and TTA-2 degree, whereas minimum TS (165.88 MPa) is attained at sample 15 of TRS-1100 rpm, WS-30 mm/min, and TTA-3 degree. The ANOVA outcome revealed that TRS is the most significant factor (23.24%) which improves the tensile property of joints, followed by a weld speed of 21.7% and a combination of tool speed and weld speed (16.17%). The increment in the tool tilt angle does not play a vital role in improving the TS value, and MINITAB -17 software helped to find a relation between the parameters in the regression equation.